Pendampingan Manajemen Organisasi Pemuda Karang Taruna Abadi Desa Sahang, Kecamatan Ngebel, Kabupaten Ponorogo - Tasya Amelia; Nafi'ah (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to determine how to empower youth by implementing Karang Taruna organizational management. Organizational management consists of various activities in the form of planning and managing organizational resources to achieve the expected goals. The type of research used in this study is ABCD, namely Asset Based Communities Development (ABCD) is a model approach in community development. This approach emphasizes the inventory of assets in the community that are considered to support community empowerment activities. The results of the study revealed that youth empowerment by implementing Karang Taruna organizational management is running quite well but cannot be said to be running optimally, this is because there are still several things that still need to be fixed and enhanced. This can be seen from various aspects (1) Strategy when planning activities in organizational management and coordination with the plan. (2) Organization, especially negotiations with Karang Taruna activity organizers according to the division of tasks and youth systems, requires careful planning so that activities can be carried out effectively. (3) This is done through efficient organization and maintaining communication. Performance in an organization cannot be separated from the contribution of all team members involved. (4) Monitor the areas of responsibility and achievements of youth groups who hold community representative positions, especially youth who are always responsible for carrying out useful activities.